Differences in the action of Inspection of Education in public, private and concerted centers - Galicia Mangas, Francisco Javier (Avances en Supervisión Educativa, 2016)
Our legal system considers the provision of educational services through public, private and maintained schools. The rules and course of action of inspection must conform to some guidelines which respect the different legal status of each type of school, but to ensure the essential content of the right to education regulated in article 27 of the Spanish Constitution.The dilemma between the rights of ownership of a school and the authority of the Administration is not always easy to resolve, but we must try to combine this autonomy of management, organisation and functioning with the application of the main principles that guarantee the right to education under conditions of equality in accordance with the Constitution and laws, as well as the existence of an education system that is characterized by general education programming, the effective involvement of all the concerned sectors, and the free and compulsory basic education.From a general perspective it can be understood that there is a gradation in the already stated intervention of administration and inspection, ranging from their wider or more extensive ability in public schools to the minimum intervention in private establishments, passing through an intermediate situation in the case of maintained centers subsidised with public funds that offer formal education.
Keywords: inspection in public; private; maintained centres; gradation in intervention